2007
DOI: 10.1002/clc.20183
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Tissue Perfusion in ST Segment Elevation Myocardial Infarction Patients Undergoing Reperfusion Strategies: Role of Adenosine

Abstract: SummaryHigh risk ST segment elevation myocardial infarction (STEMI) patients undergoing reperfusion therapy continue to exhibit significant morbidity and mortality due in part to myocardial reperfusion injury. Importantly, preclinical studies demonstrate that progressive microcirculatory failure (the "no-reflow" phenomenon) contributes significantly to myocardial reperfusion injury. Diagnostic techniques to measure tissue perfusion have validated this concept in humans, and it is now clear that abnormal tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The highest incidence of impaired tissue perfusion was observed in LAD occlusions and the frequency of this complication was independent of the method of reperfusion. Numerous studies have noted a marked discrepancy between epicardial blood flow and tissue perfusion, emphasizing that normalization of epicardial blood flow (TIMI 3) frequently did not result in adequate tissue perfusion (MBG 3) [9,25]. Studies have also demonstrated that tissue perfusion is an independent predictor of both early and late mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest incidence of impaired tissue perfusion was observed in LAD occlusions and the frequency of this complication was independent of the method of reperfusion. Numerous studies have noted a marked discrepancy between epicardial blood flow and tissue perfusion, emphasizing that normalization of epicardial blood flow (TIMI 3) frequently did not result in adequate tissue perfusion (MBG 3) [9,25]. Studies have also demonstrated that tissue perfusion is an independent predictor of both early and late mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Although TIMI flow grade and CTFC provide information regarding the patency of epicardial arteries, these methods do not assess local tissue perfusion. The MBG is relatively simple and available in all cath-labs with semiquantitative angiographic measurement of evaluating tissue perfusion and clinicians use this method more and more frequently nowadays [23,25]. Impaired tissue perfusion occurred in up to 44% of patients with ST segment elevation myocardial infarction [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenosine has been studied extensively for its vasodilatory effect when injected into the coronary arteries, and also its properties that result in inhibition of platelet aggregation and thromboemboli formation [13][14][15]. However, its short half-life, and potential side effect of atrioventricular nodal blockade and hypotension may limit its use and benefit [16].…”
Section: Standard Pharmacologic Therapiesmentioning
confidence: 99%
“…It also rapidly reverses the effect of numerous vasoconstrictors in the coronary circulation during PCI [9]. One aim of this pilot study was to assess if adenosine injection given at the time of cell administration for a subgroup of patients improved the efficacy of the cell therapy.…”
mentioning
confidence: 99%